Directed-Mutagenesis of Flavobacterium meningosepticum Prolyl-Oligopeptidase and a Glutamine-Specific Endopeptidase From Barley - Osorio, Claudia E.; Wen, Nuan; Mejías, Jaime H.; Mitchell, Shannon; von Wettstein, Diter; Rustgi, Sachin (Frontiers in Nutrition, 2020)
Wheat gluten proteins are the known cause of celiac disease. The repetitive tracts of proline and glutamine residues in these proteins make them exceptionally resilient to digestion in the gastrointestinal tract. These indigested peptides trigger immune reactions in susceptible individuals, which could be either an allergic reaction or celiac disease. Gluten exclusion diet is the only approved remedy for such disorders. Recently, a combination of a glutamine specific endoprotease from barley (EP-B2), and a prolyl endopeptidase from Flavobacterium meningosepticum (Fm-PEP), when expressed in the wheat endosperm, were shown to reasonably detoxify immunogenic gluten peptides under simulated gastrointestinal conditions. However useful, these “glutenases” are limited in application due to their denaturation at high temperatures, which most of the food processes require. Variants of these enzymes from thermophilic organisms exist, but cannot be applied directly due to their optimum activity at temperatures higher than 37°C. Though, these enzymes can serve as a reference to guide the evolution of peptidases of mesophilic origin toward thermostability. Therefore, a sequence guided site-saturation mutagenesis approach was used here to introduce mutations in the genes encoding Fm-PEP and EP-B2. A thermostable variant of Fm-PEP capable of surviving temperatures up to 90°C and EP-B2 variant with a thermostability of up 60°C were identified using this approach. However, the level of thermostability achieved is not sufficient; the present study has provided evidence that the thermostability of glutenases can be improved. And this pilot study has paved the way for more detailed structural studies in the future to obtain variants of Fm-PEP and EP-B2 that can survive temperatures 100°C to allow their packing in grains and use of such grains in the food industry.